Monitoring the Etching Process of Hi-Bi Fiber Through a Fiber Loop Mirror - Danling Wu; Jun Zhu; Hui Wang; Benli Yu (IEEE Photonics Journal)
A method for monitoring the etching process of Hi-Bi fiber is proposed and demonstrated. The birefringence of the etching fiber is accurately calculated by tracking the shift of the interference spectrum in a high-birefringence fiber loop mirror interferometer. Then, the degree of etching can be inferred by the relationship between the etching-fiber birefringence and the fiber structure. A section of PANDA fiber is used as an example to experimentally demonstrate the proposed method. The results show that the calculated birefringence is consistent with the theoretical simulation. Furthermore, four different structural states, which reflected in four different rate of change, are presented in the whole etching process of PANDA fiber. This method has the advantages of easy realization, high precision, and repeatability, and it can be used in the preparation of Hi-Bi microfiber photonic devices.